P421 'The promise of PrEP': motivations for taking PrEP among early-adopting new zealand gay and bisexual men. (14th July 2019) - Punchihewa, Tanushi; Saxton, Peter; Wiles, Janine
Abstract : Background: In 2018 amid rising HIV diagnoses, New Zealand became one of the first countries to fully fund pre-exposure prophylaxis (PrEP) through its public health system. PrEP has clear HIV prevention benefits but also potential trade-offs, namely behavioural risk compensation among gay and bisexual men (GBM). These concerns can trouble public health leadership, soften PrEP promotion and delay service re-orientation towards PrEP delivery, hampering implementation. Understanding the motivations of early PrEP adopters could address stakeholder concerns and improve PrEP roll-out. Methods: We examined data from the baseline "NZPrEP" demonstration project among 150 GBM conducted in Auckland sexual health clinics 2017–18. All participants completed a linked anonymous online survey at enrolment. Open-ended responses to questions on PrEP motivations and clinic experiences were coded in NVivo and subject to inductive thematic analysis. Secondly, using a deductive approach we applied the identified themes to the theory of planned behaviour (TPB). Results: We identified six motivations by early-adopters for taking PrEP: risky behaviour; engaging in condomless sex; altruism; risk reduction and prevention; early and free access to PrEP; and peace of mind and autonomy. These themes clearly mapped onto the three main tenets of TPB, namely behavioural beliefs, normative behaviours, and perceived behavioural control. In addition, five themes were also identified regarding PrEP implementation: accessibility; clearer communication; greater promotion; clinic attitude; and gratitude. Conclusion: Early-adopters expressed several motivations for PrEP that align with recognised public health values. Themes such as altruism (wanting to protect partners and the community as well as oneself), risky behaviours (difficulties negotiating safe sex) and peace of mind (reducing anxiety in a high HIV prevalence community) can help persuade stakeholders that PrEP is an ethical as well as an effective HIV prevention tool. Such findings are especially pertinent for government officials, general practitioners, the general public and gay communities themselves. Disclosure: No significant relationships.